ASSOCIATION OF PARENTAL BEHAVIOR IN CHOOSING SNACKS WITH NUTRITIONAL STATUS OF SCHOOL-AGE CHILDREN AT SDN MOJOLANGU 4 - Dera, Desembriani Natasya; Dewi Satiti, Ika Arum; Jayanti, Nicky Danur; Harnawati, Riska Arsita (Siklus : Journal Research Midwifery Politeknik Tegal, 2024)
Parents' behavior in selecting snacks significantly influences children's snacking habits, which are positively associated with nutritional status. The nutritional status of school-age children is influenced by several factors, including their daily eating habits at home instilled by their parents and peer-snacking behavior in the school environment. This study investigated the relationship between parents' behavior in snack selection and the nutritional status of school-age children at SDN 4 Mojolangu. The research employed an analytical correlational design with 160 respondents comprising 80 parents and 80 students in grades 1-4. Additionally, weight and height measurements were taken for the students. Statistical analysis was conducted using the Sommers'D test. The results indicate a significant relationship between parents' behavior in snack selection and the nutritional status of school-age children. The analysis of the correlation between parental behavior and nutritional status (BMI-for-age) yielded a significance value of p=0.000 (r=1.000), indicating a strong positive correlation. Meanwhile, the correlation between nutritional status (Height-for-age) showed a significance value of p=0.000 (r=0.654), demonstrating a strong positive correlation.